Oxygen and mechanical stretch in the developing lung: risk factors for neonatal and pediatric lung disease - Zhang, Emily Y.; Bartman, Colleen M.; Prakash, Y. S.; Pabelick, Christina M.; Vogel, Elizabeth R. (Frontiers in Medicine, 2023)
Chronic airway diseases, such as wheezing and asthma, remain significant sources of morbidity and mortality in the pediatric population. This is especially true for preterm infants who are impacted both by immature pulmonary development as well as disproportionate exposure to perinatal insults that may increase the risk of developing airway disease. Chronic pediatric airway disease is characterized by alterations in airway structure (remodeling) and function (increased airway hyperresponsiveness), similar to adult asthma. One of the most common perinatal risk factors for development of airway disease is respiratory support in the form of supplemental oxygen, mechanical ventilation, and/or CPAP. While clinical practice currently seeks to minimize oxygen exposure to decrease the risk of bronchopulmonary dysplasia (BPD), there is mounting evidence that lower levels of oxygen may carry risk for development of chronic airway, rather than alveolar disease. In addition, stretch exposure due to mechanical ventilation or CPAP may also play a role in development of chronic airway disease. Here, we summarize the current knowledge of the impact of perinatal oxygen and mechanical respiratory support on the development of chronic pediatric lung disease, with particular focus on pediatric airway disease. We further highlight mechanisms that could be explored as potential targets for novel therapies in the pediatric population.